2021
DOI: 10.1371/journal.pone.0252290
|View full text |Cite
|
Sign up to set email alerts
|

A proposed population-health based metric for evaluating representativeness of air quality monitoring in cities: Using Hong Kong as a demonstration

Abstract: City air quality monitoring (AQM) network are typically sparsely distributed due to high operation costs. It is of the question of how well it can reflect public health risks to air pollution given the diversity and heterogeneity in pollution, and spatial variations in population density. Combing high-resolution air quality model, spatial population distribution and health risk factors, we proposed a population-health based metric for AQM representativeness. This metric was demonstrated in Hong Kong using hour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…In the headed study, hourly PM 2.5 concentration data, from 1 January 2014 to 31 December 2021, were obtained from all 16 air quality monitoring stations (AQMS) in Hong Kong (Figure 1 ). These hourly PM 2.5 concentrations are based on high‐accuracy gravimetric sampling, using the Thermal Scientific Model 1405‐DF Filter Dynamics Measurement System (FDMS) from the Hong Kong Environment Protection Department (HKEPD) (Hohenberger et al., 2021 ; G. Shi et al., 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…In the headed study, hourly PM 2.5 concentration data, from 1 January 2014 to 31 December 2021, were obtained from all 16 air quality monitoring stations (AQMS) in Hong Kong (Figure 1 ). These hourly PM 2.5 concentrations are based on high‐accuracy gravimetric sampling, using the Thermal Scientific Model 1405‐DF Filter Dynamics Measurement System (FDMS) from the Hong Kong Environment Protection Department (HKEPD) (Hohenberger et al., 2021 ; G. Shi et al., 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Another health risk study concluded that the AQHI system in Hong Kong helped to reduce the cardiovascular hospitalization for elderly population ( Mason et al, 2020 ). This health risk model was also applied to evaluate the representativeness of air quality monitoring network ( Hohenberger et al, 2021 ) and estimate the high-resolution exposure distribution ( Che et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%